Volume 8B: 45th Mechanisms and Robotics Conference (MR) 2021
DOI: 10.1115/detc2021-69957
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Planning for a 3-SPS-U Tensegrity Mechanism

Abstract: This article presents the actuation strategy of a 2-DOF tensegrity type mechanism that employs three tension springs and a passive universal joint. This mechanism is proposed to be incorporated as an articulation unit for a piping inspection robot in order to overcome pipe bends and junctions. In the event of a junction, external actuations are required to allow the mechanism as well as the robot to follow a certain direction. Using DC-motors coupled with encoders, experiments are carried out on a test bench o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The actual prototype that will be incorporated with the piping-inspection robot has the design parameters r f as 11 mm and h = 0.6 [16]. As an experimental validation is carried out in the upcoming section, a scaled value of r f = 56.7 mm for h = 0.6 is chosen for the singularity analysis [25]. As the constraint equations require joint limits for analysis, the minimum and maximum lengths for each prismatic spring are set as l min = 40 mm and l max = 106 mm.…”
Section: Results Of Singularity Analysis Using the Cad Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual prototype that will be incorporated with the piping-inspection robot has the design parameters r f as 11 mm and h = 0.6 [16]. As an experimental validation is carried out in the upcoming section, a scaled value of r f = 56.7 mm for h = 0.6 is chosen for the singularity analysis [25]. As the constraint equations require joint limits for analysis, the minimum and maximum lengths for each prismatic spring are set as l min = 40 mm and l max = 106 mm.…”
Section: Results Of Singularity Analysis Using the Cad Algorithmmentioning
confidence: 99%
“…This actuation is carried out through the cables that pass through the springs of the mechanism. The pose variables and the articular variables for the mechanism are given by q = [η, φ] and ρ = [l 1 , l 2 , l 3 ] [25]. The length of the springs is calculated using Equations (16a)-(16c) in the Euler space.…”
Section: Trajectory Generationmentioning
confidence: 99%
“…Thus, a control law will be implemented which takes into account the friction and cable elasticity factors similar to the control strategy of a tensegrity structure proposed by Fasquelle et al [25]. Also, advanced controllers such as the EtherCAT will be employed for the experiments when compared to a simple BeagleBone black card that was employed for the single-stage model in [21]. The EtherCAT allows controlling several components at the same time from a central unit.…”
Section: Discussionmentioning
confidence: 99%
“…The Type-3 singularities occur only when there exist both serial and parallel singularities, which is once again not possible for the mechanism. Based on the experiments conducted on the tensegrity mechanism in [21], it was observed that one or two of the prismatic springs reach their minimum length at two specific positions referred to as:…”
Section: Analysis Of Workpace For the Hybrid Mechanismmentioning
confidence: 99%
See 1 more Smart Citation